The Cytological and Histopathological correlation of Thyroid Lesions - Syed, Madiha; Noreen Akhtar; Maryam Hameed; Sajid Mushtaq; Asif Loya; Usman Hassan; Muddassar Hussain (Journal of the Pakistan Medical Association, 2022)
Objective: To determine accuracy of cytological diagnosis in comparison with the corresponding histopathological diagnosis of thyroid lesions. Method: The retrospective study was conducted at the Shaukat Khanum Memorial Cancer Hospital, Lahore, Pakistan, and comprised data from January to December 2017 of all in-patient cases of thyroid cytology with their histopathological diagnosis. Both Hematoxylin and eosin stain slides and cytological smears were reviewed. True negative, true positive, false negative and false positive cases were marked using the criteria defined in TABLE 1. Results: Of the total 36 cases, 5(13.9%) were non-diagnostic or unsatisfactory for cytological assessment. Cytological diagnosis achieved sensitivity of 82.3%, specificity 64.3%, positive predictive value 73.6%, negative predictive value 75%, false positive rate 35.7% and false negative rate 17.6%. The diagnostic accuracy of cytological diagnosis was 63.9%. Conclusion: There was significant cytological and histopathological concordance of thyroid lesions. Key Words: FNAC, fine needle aspiration cytology, Bethesda system, Thyroid, Cytology, Histopathology. Continuous..